Reliability of Chinese web-based ocular surface disease index questionnaire in dry eye patients: a randomized, crossover study - Xin-Mei Zhang; Lan-Ting Yang; Qing Zhang; Qing-Xia Fan; Can Zhang; Yue You; Chen-Guang Zhang; Tie-Zhu Lin; Ling Xu; Salissou Moutari; Jonathan E. Moore; Emmanuel E. Pazo; et al. (International Journal of Ophthalmology, 2021)
AIM: To assess the reliability of web-based version of ocular surface disease index in Chinese (C-OSDI) on clinically diagnosed dry eye disease (DE) patients. METHODS: A total of 254 Chinese participants (51% male, 129/254; mean age: 27.90±9.06y) with DED completed paper- and web-based versions of C-OSDI questionnaires in a randomized crossover design. Ophthalmology examination and DED diagnosis were performed prior to the participants being invited to join the study. Participants were randomly designated to either group A (paper-based first and web-based second) or group B (web-based first and paper-based second). Final data analysis included participants that had successfully completed both versions of the C-OSDI. Demographic characteristics, test-retest reliability, and agreement of individual items, subscales, and total score were evaluated with intraclass correlation coefficients (ICC), Spearman rank correlation, Wilcoxon test and Rasch analysis. RESULTS: Reliability indexes were adequate, Pearson correlation was greater than 0.8 and ICCs range was 0.827 to 0.982; total C-OSDI score was not statistically different between the two versions. The values of mean-squares fit statistics were very low compared to 1, indicating that the responses to the items by the model had a high degree of predictability. While comparing the favorability 72% (182/254) of the participants preferred web-based assessment. CONCLUSION: Web-based C-OSDI is reliable in assessing DED and correlation with the paper-based version is significant in all subscales and overall total score. Web-based C-OSDI can be administered to assess individuals with DED as participants predominantly favored online assessment.